PEMANFAATAN SAMPAH PLASTIK MANJADI PAVING BLOK DI DESA HAJIMENA–NATAR,LAMPUNG SELATAN - Yuli Ambarwati; Syaiful Bahri; Valennisa Qunifah; Lina Marlina; Sutopo Hadi; Aspita Laila; John Hendri (Universitas Mataram, 2022)
Hajimena Village is part of the Natar District which is directly adjacent to the Bandar Lampung City area, so that garbage disposal also enters from Bandar Lampung. The introduction and application of the 3R (Reduce, Reuse, Recycle) principle or the reduction, reuse and recycling of waste is one of the approaches in waste management. Inorganic waste can be converted into handicrafts that can be sold, especially plastic waste can be or processed into paving blocks. The Department of Chemistry Faculty of Mathematics and Natural Sciences University of Lampung, Community Service Team carried out community service activities aimed at increasing public awareness and participation in managing waste independently, reducing plastic waste and being a source of income for BUMDES. The activity of making paving blocks with variations of plastic waste, used oil, rice husks, and sand using simple technology and tools. The results of community service activities can be seen from the evaluation results in the form of measuring the achievement of specific instructional goals (ICT) from activities carried out using pre-test and post-test given to participants. The results show that there has been an increase in ICT for each participant after this service activity was carried out, it can be seen that each ICT has increased with an average increase of about 60.4%. This shows that public knowledge about plastic waste has increased significantly. So that the processing of plastic waste can be an opportunity to increase the income of the Hajimena village community.